Oral health and oral diseases in pregnancy: a multicentre survey of Italian postpartum women. (5th May 2013) - Villa, A; Abati, S; Pileri, P; Calabrese, S; Capobianco, G; Strohmenger, L; Ottolenghi, L; Cetin, I; Campus, GG
Abstract Background The aim of this study was to explore the oral hygiene practices and oral health status of Italian postpartum women. Methods A self‐administered questionnaire assessed socio‐demographic information, oral hygiene habits and frequency of dental visits. All women received a thorough oral examination within five days after delivery. Logistic regression models were used to estimate odds ratios and 95% confidence intervals for exposures of interest and the presence of 'severe' periodontitis. Results Seven hundred and fifty women participated in the study; 99.1% brushed their teeth everyday and 59.9% visited the dentist annually. The mean frequency of sites with bleeding on probing was 16.1% and the median clinical attachment level was 2.1 mm. The mean caries experience score (DMFT) was 8. Severe periodontal disease was present in 21.9% of individuals. Patients who reported visiting a dentist only when in pain and women with three dental caries or more were significantly more likely to have periodontitis (OR: 1.6; 95% CI: 1.1–2.2; p < 0.05 and OR: 2.3; 95% CI: 1.5–3.5; p < 0.01, respectively). Conclusions Given the possible association between maternal and infant oral health, and between periodontal infection and general health, antenatal care providers should collaborate with dentists to encourage all pregnant women to comply with the oral health professionals' recommendations regarding appropriate dental brushing techniques and the importance of dental visits.